PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN KARAKTERISTIK TUJUAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN LINGKUNGAN KERJA NON FISIK SEBAGAI VARIABEL MODERASI - Iwan Koerniawan; Eka Satria Wibawa (Universitas Sains dan Teknologi Komputer, 2019)
The purpose of this study is to analyze and provide empirical evidence about the influence of budgeting participation and budget goal characteristics on managerial performance with a non-physical work environment as moderation. Population variables in this study are all leaders and financial officers in private vocational schools in the city of Semarang listed in the structure of the division of school work in 2016 which amounted to 14 vocational high schools and each was taken by 3 people so that there were 42 respondents, while the sampling technique used the census method. Data analysis method used is Regression Moderation Analysis (MRA) Hypothesis 1 test results note that the value of t arithmetic = 3.012> t table = 1.694 with a number of significance = 0.003 <α = 0.05 (significant), so the hypothesis (H1) that participation budgeting has a positive effect. on proven managerial job performance. Regression coefficient β1 = 0.567 (positive sign), it can be interpreted that the higher the participation in budgeting, the higher the managerial performance. Hypothesis 2 testing is known that the value of t = 2.723> t table = 1.694 with a significance value = 0.010 <α = 0.05 (significant), so the hypothesis (H2) that the characteristics of the budgetary objectives have a positive effect on managerial performance of the work proved. Stepwise coefficient = 0.279 (benchmark), can be interpreted more clearly the characteristics of the managerial level budget objectives. Testing hypothesis 3 is known that the value of t 2.484> t table = 1.694 with a significance value = 0.026 <α = 0.05 (significant), so the hypothesis (H3) that the work environment is not moderate, moderate moderate positive positive effect on budget participation on managerial work performance proven. Testing hypothesis 4 is known that the value of t arithmetic 2.333> t table = 1.694 with the number of significance = 0.032 <α = 0.05 (significance nt). Thus the hypothesis (H4) that the non-physical work environment positively influences the characteristics of budgetary goals on proven managerial work performance. Interaction test results show β4 = 0.163 (positive sign), it can be interpreted that the existence of a non-physical work environment that is conducive will strengthen the influence of the characteristics of the budget objectives on managerial work performance. Keywords: Budget participation, characteristics of budget objectives, non-physical work environment, managerial work performance